Technology and symbolism in ashaninka basketry - Rojas Zolezzi, Enrique Carlos (2021)
This article explains the role of technological and ethnobotanical knowledge, the aesthetic and symbolic aspects of basketwork in creating the material basis of the gender division of labor among the ashaninka on the Peruvian Amazon.